Control the Epithelial Barrier: A Pivotal First Line of Defense - Catherine M McKay; Derek M McKay (Canadian Journal of Gastroenterology)
Lumen-derived material gains access to the mucosa by permeating between adjacent epithelial cells (ie, paracellular pathway), by transcytosis across the apical and basolateral cell membranes (ie, transcellular pathway) or by exploiting breaks or erosions in the epithelium that may, for example, result from inflammation. Increased epithelial permeability (or decreased barrier function) has repeatedly been demonstrated in a variety of gut disturbances; notably, in inflammatory bowel disease (IBD). There has been an exponential increase in our knowledge of the structural elements that comprise the epithelial barrier, and of the intrinsic factors (eg, cytokines) and external stimuli (eg, bacterial toxins) that can either perturb or enhance epithelial permeability. Canadian researchers have been very active in the study of epithelial permeability and have been responsible for major advances in the field, documenting increased permeability in patients with ulcer disease and IBD and some of their first degree relatives (as well as before onset of overt inflammation), and elucidating mechanisms of stress-induced and cytokine-induced increases in permeability (1-8). A recent study from Scott et al (9) continues this impressive tradition.